2004
DOI: 10.1186/1471-227x-4-5
|View full text |Cite
|
Sign up to set email alerts
|

Management of acute renal colic in the UK: a questionnaire survey

Abstract: Background: There is great variation in the Accident and Emergency workload and location of Urology services in UK hospitals. This study investigated the relationship of the initial management of acute renal colic with the department workload plus local facilities including location of X-ray and urology services in UK Accident and Emergency (A&E) departments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 13 publications
0
9
0
2
Order By: Relevance
“…[9] In this double-blind, randomized study, no statistically significant differences were found between the groups in terms of effectiveness or side effects. Lasoye et al [21] identified that the most common treatment agent for acute renal colic in the emergency departments and urology clinics in England is diclofenac sodium. Yilmaz et al divided 114 patients with acute renal colic into 3 groups and treated them with 3 different alpha-blocker therapies.…”
Section: Discussionmentioning
confidence: 99%
“…[9] In this double-blind, randomized study, no statistically significant differences were found between the groups in terms of effectiveness or side effects. Lasoye et al [21] identified that the most common treatment agent for acute renal colic in the emergency departments and urology clinics in England is diclofenac sodium. Yilmaz et al divided 114 patients with acute renal colic into 3 groups and treated them with 3 different alpha-blocker therapies.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the choice of initial analgesia was found to vary significantly depending on the annual number of patients seen in an emergency department. Among emergency departments categorized as small, 21% utilized opiates as first-line medications compared to 2.9, 5.7, and 12.5% of medium, large, and very large departments, respectively (P = 0.011) [12]. The implementation of a standardized analgesic protocol comprised of a ketorolac and morphine combination resulted in a 49% reduction in time to pain relief among patients seen in the emergency department for renal colic, compared to a matched cohort receiving ad hoc care.…”
Section: Non-steroidal Anti-inflammatory Drugs and Narcoticsmentioning
confidence: 91%
“…Fifty-five percent of those with recurrent stones have a family history of urolithiasis [3] and having such a history increases the risk of stones by a factor of three [4]. Upon presentation to the A&E department, suspected acute renal colic patients must have a clinical examination and radiological investigations to confirm the diagnosis [5].…”
Section: Introductionmentioning
confidence: 99%
“…The best imaging study to confirm the diagnosis of a urinary stone in a patient with acute flank pain is unenhanced, helical CT of the abdomen and pelvis [6]. If CT is unavailable, plain abdominal radiography should be performed, since 75 to 90 percent of urinary calculi are radiopaque [5]. Although ultrasonography has high specificity (greater than90 percent), its sensitivity is much lower than that of CT, typically in the range of 11 to24 percent [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation